Modeling multiphase materials processes gas-liquid systems - Iguchi, Manabu; Ilegbusi, O. J.; SpringerLink (Online service). (New York Springer, 2011)
Quot;Modeling Multiphase Materials Processes: Gas-Liquid Systems" describes the methodology and application of physical and mathematical modeling to multi-phase flow phenomena in materials processing. The book focuses on systems involving gas-liquid interaction, the most prevalent in current metallurgical processes. The performance characteristics of these processes are largely dependent on transport phenomena. This volume covers the inherent characteristics that complicate the modeling of transport phenomena in such systems, including complex multiphase structure, intense turbulence, op.
Modeling Multiphase Materials Processes; Preface; Contents; 1 Introduction; 2 Turbulence Structure of Two-Phase Jets; 3 The Coanda Effect; 4 Interfacial Phenomena; 5 Swirling Flow and Mixing; 6 Slag-Metal Interaction; 7 Surface Flow Control; 8 Two-Phase Flow in Continuous Casting; 9 Modeling Gas-Liquid Flow in Metallurgical Operations; 10 Numerical Modeling of Multiphase Flows in Materials Processing; 11 Review of Nanoscale and Microscale Phenomena in Materials Processing; Appendix 1; Appendix 2; Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Multiphase flow -- Mathematical models; Electronic books